Does employment uncertainty particularly impact fertility of children of North African immigrants in France? A gender perspective - (:unkn) unknown (My University, 2018)
This paper investigates whether unemployment and insecure employment lead to delaying first childbearing in France, and whether these impacts are likely to differ between children of immigrants from North Africa and natives across genders. Data come from pooling two cohorts of French school-leavers followed over 7–10 years. Findings show that women of North African descent have a first child later than native women, whereas results for men are not significantly ethnic origin-differentiated. Unemployment and non-permanent employment are related to postponement of fertility for both men and women. Current unemployment affects the children of immigrants from North Africa more than their counterparts with no direct migration background. Persistent unemployment does not have any significant effect on childbearing for the women of North African immigrant descent, while it strongly reduces that of the men. While employment uncertainty thus tends to delay first parenthood, its impact seems to occur more through the timing of couple formation than through the timing of conception among children of immigrants from North Africa.
Keywords: African Research